A role of cathepsin L gene in innate immune response of crayfish (Procambarus clarkii). Issue 71 (December 2017) - Dai, Li-Shang; Chu, Sheng-Hui; Yu, Xiao-Min; Li, Yan-Yan
Abstract: Cathepsin L is one of the crucial enzyme superfamilies and involved in the immune responses. In the present study, cathepsin L gene from the red crayfish Procambarus clarkii, named PcCTSL, was cloned and characterized. The cDNA fragment of PcCTSL was 1026 bp in length, which encoded a putative protein of 341 amino acid residues with a molecular weight of 37.884 kDa. The theoretical isoelectric point was 5.218. The prepro-cathepsin L was comprised of a typical signal peptide (Met1 -Ala18 ), a prodomain proregion peptide (Trp29 -Phe89 ) and a mature peptide (Leu124 -Leu340 ). Homology analysis indicated that PcCTSL exhibited 53.2%–87.1% identity to other selected species. The recombinant protein of PcCTSL was successfully expressed in Escherichia coli and rabbit anti-PcCTSL polyclonal antibodies were prepared. Real-time quantitative reverse transcription-PCR (qPCR) analysis revealed that the PcCTSL was expressed in all examined tissues, while the greatest mRNA level was observed in hepatopancreas. The expression of PcCTSL mRNA was clearly up regulated in hepatopancreas after challenge by lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (Poly I:C). RNA interference of PcCTSL affected the gene expression of members of the Toll pathway. Our results suggest that the PcCTSL may play an important role to defend P. clarkii against the pathogens infection. Highlights: A cathepsin L gene from Procambarus clarkii (PcCTSL) was identified and characterized for the first time. A rabbit anti-PcCTSL polyclonal antibody was prepared. Transcripts and expression levels of PcCTSL in the hepatopancreas were detected after LPS and Poly I:C challenge. RNA interference of PcCTSL affected the gene expression of members of the Toll pathway.